2021
DOI: 10.1111/aswp.12224
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CPI‐based co‐parenting education programs in Hong Kong: Implications for social work

Abstract: This article reports an evaluation study of co‐parenting education services in a pilot project on co‐parenting support services in Hong Kong. Based on the Cooperative Parenting Institute (CPI) model, there are two levels of education program: Level 1 is an information‐based program delivered through talks or lecture format; and Level 2 is participatory, interactive workshops. The study results would provide preliminary support to the effectiveness of the CPI‐based education programs in reducing inter‐parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The reliability of the subscale containing items related to conflict was α = 0.95 at pre‐test and α = 0.96 at post‐test. Overall, both levels of the program demonstrated a significant reduction in co‐parental conflict based on participants' self‐reports ( t = 3.167, p < 0.01 and t = 5.89, p < 0.01) (Lau, 2021). No effect sizes for this study were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…The reliability of the subscale containing items related to conflict was α = 0.95 at pre‐test and α = 0.96 at post‐test. Overall, both levels of the program demonstrated a significant reduction in co‐parental conflict based on participants' self‐reports ( t = 3.167, p < 0.01 and t = 5.89, p < 0.01) (Lau, 2021). No effect sizes for this study were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…Physical education evaluation is the process of using all feasible technical means to measure the factors affecting the physical education process and their effects according to the physical education objectives, and to make value judgments [18]. The essence of physical education evaluation is to judge the value of physical education activities in terms of influence and effect t [19].…”
Section: The General Idea Of Pe Teaching Evaluationmentioning
confidence: 99%